2014
DOI: 10.1016/j.expneurol.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A survey from 2012 of evidence for the role of neuroinflammation in neurotoxin animal models of Parkinson's disease and potential molecular targets

Abstract: Parkinson’s disease (PD) is a neurodegenerative movement disorder that results from the progressive loss of dopaminergic neurons in the midbrain substantia nigra pars compacta (SNpc). The specific molecular events that cause PD are currently not known; however, progress to better understand PD pathogenesis has been made using various animal models of the disease. In this review, we have highlighted reports from 2012 in which neurochemical/neurotoxins have been used in rodents to specifically address the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 56 publications
1
36
1
2
Order By: Relevance
“…MPPþ utilizes the dopamine transporter to selectively target DA neurons where MPPþ inhibits mitochondrial complex I causing increased ROS and neuron demise. 20,50 However, the mechanism of death may be more complicated in light of evidence implicating inflammatory response in MPTP toxicity. MPTP treatment of mice leads to loss of DA neuron cell bodies in the SN and axon terminals in the striatum as well as reduced dopamine levels.…”
Section: Mptp and Neuroinflammationmentioning
confidence: 99%
See 3 more Smart Citations
“…MPPþ utilizes the dopamine transporter to selectively target DA neurons where MPPþ inhibits mitochondrial complex I causing increased ROS and neuron demise. 20,50 However, the mechanism of death may be more complicated in light of evidence implicating inflammatory response in MPTP toxicity. MPTP treatment of mice leads to loss of DA neuron cell bodies in the SN and axon terminals in the striatum as well as reduced dopamine levels.…”
Section: Mptp and Neuroinflammationmentioning
confidence: 99%
“…Evidence also suggests that PD modeling neurotoxins such as MPTP facilitate DA neuron loss at least in part by induction of inflammatory response. 20 Additionally, in mice, enhanced inflammation has been shown to recapitulate a-synuclein aggregation and oxidation in affected neurons. 18,21 A large clinical study also reported that discontinuation of lipophilic statins correlated with an elevated incidence of PD.…”
Section: Inflammation and Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…This inflammatory model of PD suggest that inflammatory stress can manifest in DA neuron loss likely through infiltration of peripheral leukocytes. Related to the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) PD model, it has been described that this neurotoxin facilitate dopamine neuronal loss at least in part by induction of inflammatory response [42]. Also, in mice, enhanced inflammation has been shown to recapitulate α-synuclein aggregation and oxidation in affected neurons [43].…”
Section: Introductionmentioning
confidence: 99%